CONSUMPTION AND IMPACT SUGAR- SWEETENED BEVERAGES IN INDONESIA BASED ON INDIVIDUAL FOOD CONSUMPTION SURVEY - made dewi SUSILAWATI (Jurnal Vokasi Kesehatan, 2019)
The need for sugar increases every year, especially demand from the food and beverage industry sector. Sugar-sweetened beverages (SSBs) are a type of beverage that is added or contains sugar such as sucrosa or fructosa (free-sugar). The result of Basic Health Research (Riskesdas) 2013 showed that residant aged ≥ 10 year consumed sugar- sweetened food or beverage ≥ 1 times every day at 53.1 percent.  Increasingly by 61.27 percent for residents aged ≥ 3 years based on Basic Health Research (Riskesdas) 2018. Data analysis used Individual Food Consumption Survey (SKMI) 2014. The average energy intake of drinks consumed by all respondents is 122 calories / day with an estimated average sugar intake of around 31 grams / day or ± 2.5 tablespoons / day. Estimation of SSBs intake more increasing with age in men but did not occur in women. More than 30 percent respondens consumed tea packaging (liquid tea) or  brewed tea (tea leaves) that was added sugar. The average energy intake is 87 cal / day with an estimated sugar intake of 22 grams / day or equivalent to ± 2 tablespoons per day. Several studies have shown the impact of SSBs  related to the incidence of obesity and diabetes mellitus. Intake SSBs every day will increase 0.05-0.06 point of body mass index. The risk of diabetes mellitus is higher in people who consume sugary drinks 1-2 times per day than people who consume less than 1 time per month.